Swimming anatomy and lower back injuries in competitive swimmers: A narrative review - Hsu, C.; Krabak, B.; Cunningham, B.; Borg-Stein, J. (Sports Health: A Multidisciplinary Approach, 2024)
Context: Competitive swimmers are at high risk of overuse musculoskeletal injuries due to their high training volumes. Spine injuries are the second most common musculoskeletal injury in swimmers and are often a result of the combination of improper technique, high loads on the spine in strokes that require hyperextension, and repetitive overuse leading to fatigue of the supporting trunk muscles. The purpose of this review is to summarize the current evidence regarding swimming biomechanics, stroke techniques, and common injuries in the lumbar spine to promote a discussion on the prevention and rehabilitation of lower back injuries in competitive swimmers.